2018
DOI: 10.4172/2157-7439.1000496
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-based Nanoparticle for Dye Sensitized Solar Cells with Improved Efficiency

Abstract: Dye sensitized solar cells were fabricated with DyLight680 (DL680) dye and its corresponding europium conjugated dendrimer, DL680-Eu-G5PAMAM, to study the effect of europium on the current and voltage characteristics of the DL680 dye sensitized solar cell. The dye samples were characterized by using Absorption Spectroscopy, Emission Spectroscopy, Fluorescence lifetime and Fourier Transform Infrared measurements. Transmission electron microscopy imaging was carried out on the DL680-Eu-G5PAMAM dye and DL680-Eu-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… 1 3 Due to their multivalent and monodisperse character, dendrimers have stimulated wide interest in the field of chemistry, physics, and biology. 4 Some recent applications have been reported in the literature especially in the fields of drug delivery, 5 7 photodynamic therapy, 8 electronics, 9 catalysis, 10 12 and water purification. 13 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 3 Due to their multivalent and monodisperse character, dendrimers have stimulated wide interest in the field of chemistry, physics, and biology. 4 Some recent applications have been reported in the literature especially in the fields of drug delivery, 5 7 photodynamic therapy, 8 electronics, 9 catalysis, 10 12 and water purification. 13 …”
Section: Introductionmentioning
confidence: 99%
“…1−3 Due to their multivalent and monodisperse character, dendrimers have stimulated wide interest in the field of chemistry, physics, and biology. 4 Some recent applications have been reported in the literature especially in the fields of drug delivery, 5−7 photodynamic therapy, 8 electronics, 9 catalysis, 10−12 and water purification. 13 In the past few years, some glycerol-based dendrimers derived from polypropylenimine (PPI) and polyamidoamine (PAMAM) dendrimers were developed and used in catalysis and encapsulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that conjugated dendrimer NPs based dye has provided over 20% more efficient than without conjugation. [ 106 ] From the aforementioned discussion, one may conclude that a continuous research on dye‐sensitized solar cells (natural, and synthetic dye based) is increasing interest and more prominent improvement toward solar cell parameters may achieve in the future and consequently, DSSC will gain more attention in the renewable energy sector.…”
Section: Current Trends In Dsscsmentioning
confidence: 99%
“…The electrodes were prepared according to a previously published procedure with some modifications [27][28][29][30]. The working electrode was prepared by depositing a thin film of TiO 2 on the conductive side of a fluorine doped tin oxide (FTO) glass slide using a spin coater and the film annealed at 380 °C for 2 hours.…”
Section: Fabrication Of Dsscsmentioning
confidence: 99%